Trailing Pahang’s heritage - Aisyah Hanum, Abu Bakar (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
25 September 2010. Trailing Pahang's Heritage was the primary idea. Thus, in collaboration with Majlis Bekas Wakil Rakyat (MUBARAK) and Pahang State Government, Centre for Modern Languages and Human Sciences (CMLHS) and Universiti Malaysia Pahang (UMP) held a prestigious two-day programme "Wacana Mengingati Sejarah: Ke Arah Kecemerlangan Masa Depan" (A Discourse in Reminiscing History: Towards Future Excellence). It was one of the programme organised in conjunction with the 80th birthday celebration of Sultan Pahang, HRH Sultan Haji Ahmad Shah Al-Musta'in Billah Ibni Al-Marhum Sultan Abu Bakar Ri'ayatuddin Al-Mu'Adzam Shah.